Persistence of hepatitis B surface antibody and immune memory to hepatitis B vaccine among medical college students in Madinah - Waleed Mahallawi (Annals of Saudi Medicine, 2018)
BACKGROUND: Globally, about 300 million people are infected with hepatitis B virus (HBV). Among the effective approaches to fight HBV infection is immunization. In 1989, an obligatory hepatitis B vaccine program was launched in Saudi Arabia. OBJECTIVE: Assess hepatitis B surface antibody (anti-HBs) levels among the medical students before and after receiving booster doses of HBV vaccine. DESIGN: Cross-sectional. SETTING: Taibah University. SUBJECTS AND METHODS: Students born between 1993 and 1995 were recruited in this study from the Occupational Health Clinic. Students were screened for anti-HBs levels using chemiluminescent microparticle immunoassay (CMIA) before and after booster HBV vaccine doses. MAIN OUTCOME MEASURES: Anti-HBs levels before and after booster doses. SAMPLE SIZE: 335. RESULTS: About half of participants (n=164, 49%) had protective anti-HBs levels (≥10 mIU/mL) to the original primary series of HBV vaccine and received no booster doses. The remaining 171 (51%) participants were at risk of HBV infection since their anti-HBs levels were <10 mIU/mL, despite having received the original primary HBV vaccine. The levels of anti-HBs were higher in female than in male students (P<.001). In addition, female students showed a stronger humoral immune response to the booster vaccine than male students (P<.001). When participants were given the three boosters, most participants (98.3%) showed anti-HBs levels of ≥10 mIU/mL. The results also showed a strong correlation between pre-booster and post-booster anti-HBs levels in the ≥10 mIU/mL group (r2=0.52, P<.001) but not in <10 mIU/mL group (r2= 0.003, P=.53). CONCLUSION: A considerable portion of the participants (about 51%) were at risk of HBV infection since their anti-HBs levels were <10 mIU/mL. Booster doses significantly trigger memory immune response and this ensured their protection against the virus. Pre-booster anti-HBs level are a good predictive of post-booster anti-HBs levels in ≥10 mIU/mL group. LIMITATIONS: The sample size was small. Shortage of collaborators. CONFLICT OF INTEREST: None.